Halal and Haram in Islam: Interpretations, Prohibitions, and Dietary Considerations - Gul, Maria; Farida Begum (Journal of Islamic and Religious Studies, 2024)
The Quran, as the divine source of Islamic teachings, addresses various aspects of a Muslim's life, prominently including dietary laws that classify foods as halal (permissible) or haram (forbidden). These laws, a fundamental part of Sharia law, extend to various aspects such as Hajj, contracts, and consumption practices. The determination of halal and haram is deeply rooted in the Quran, Hadith, and scholarly consensus, with diverse interpretations about their extent. Some assert that everything is halal unless explicitly prohibited by Shariah, while others hold the opposite view. Historically, the Quran explicitly identifies 13 items as halal and another 13 as haram. Understanding these dietary laws is not just a matter of religious obligation but also of practical importance for every Muslim, as they significantly influence daily life, health, and well-being. Furthermore, an Islamic state has to ensure its citizens have access to halal food sources. This paper delves into the foundational texts, historical context, and societal implications of halal and haram dietary laws. It underscores their pivotal role in shaping a Muslim's consumption practices and the broader societal responsibilities in promoting halal food systems.